The Potential of Nostoc Cyanobacteria in Food Fortification: A Systematic Review with Experimental Evidence - Rodriguez Carrillo, Sol Angel Alfredo; Castillo Castillo, Mayra Yameli; Calle Ramos, Damaris; Crespin Guzmán, Yilbert Leyssin; Ramos Ynga, Cinthia Elizabeth; Yupanqui Apolinario, Eduardo; Velasco Colán, Juan (LACCEI, 2025)
The aim of this study was to identify and evaluate the incorporation of cushuro cyanobacteria as a food fortifier to improve nutrition in vulnerable populations. A systematic review was conducted following the PRISMA protocol, covering research published between 2010 and 2024, with a total of 23 studies selected. Additionally, an experimental methodology was employed, including infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) to analyze the chemical composition and morphology of Cushuro colonies. The results classified its components into three main groups: hydrocolloids, bioactive molecules, and minerals. In fortified foods, cushuro proved to be versatile and technologically viable, significantly increasing the protein and mineral content in various products without altering organoleptic properties when used at substitution levels between 5% and 10%. Local studies reported moderate sensory acceptability (around 50%), although the intention to recommend was high (over 80%), attributed to its nutritional benefits. The main barriers identified were changes in taste and skepticism about its properties. In conclusion, cushuro emerges as a sustainable and promising resource to address nutritional challenges and promote food security in vulnerable populations.